Pengembangan Buku Ajar Kearifan Lokal Malang Raya pada Pembelajaran Tematik SIswa kelas IV SD - Havindah Salsabila; Arina Restian; Ima Wahyu Putri Utami (SAP (Susunan Artikel Pendidikan), 2021)
Based on the results of observations and interviews with 4th’s grade teacher at SDN 1 Sidorahayu Wagir that had been conducted on January 18, 2021, there was problem in the learning process, namely the number of students who were less enthusiastic in reading. This affected student’s learning outcomes so that the learning outcomes were less than optimal and there were many students who were not familiar with local wisdom in Malang. To see these problems can be overcome by developing a textbook to attract student’s interest in learning through the introduction of local wisdom. So it can increase the spirit of learning as well as maintain and preserve local wisdom in their area where they live. This research uses Research and Development (R&D) with ADDIE method, including Analyze, Design, Development, Implementation and Evaluation. The result showed that the use Local Wisdom of Malang textbooks in 4th grade of thematic learning at SDN 1 Sidorahayu Wagir could motivate students to learn, especially reading.